Effects of cutaneous administration of an over-the-counter menthol cream during temperate-water immersion for exercise-induced hyperthermia in men - Wang, Gang; Hurr, Chansol (Frontiers in Physiology, 2023)
Hyperthermia impairs various physiological functions and physical performance. We examined the effects of cutaneous administration with an over-the-counter (OTC) analgesic cream containing 20% methyl salicylate and 6% L-menthol during temperate-water immersion (TWI) for exercise-induced hyperthermia. In a randomized crossover design, twelve healthy males participated in both of two experiments. Firstly, participants underwent a 15-min TWI at 20°C with (CREAM) or without (CON) cutaneous application of an analgesic cream. Cutaneous vascular conductance (CVC) was measured using laser doppler flowmetry during TWI. In a subsequent experiment, same participants performed a 30-min strenuous interval exercise in a heated (35°C) environment to induce hyperthermia (~39°C), which was followed by 15 minutes of TWI. Core body temperature, as measured by an ingestible telemetry sensor, and mean arterial pressure (MAP) were measured. CVC and %CVC (% baseline) were higher during TWI in CREAM than in CON (Condition effect: p=0.0053 and p=0.0010). An additional experiment revealed that core body heat loss during TWI was greater in CREAM than in CON (Cooling rate: CON 0.070±0.020 vs. CREAM 0.084±0.026°C/min, p=0.0039). A more attenuated MAP response was observed during TWI in CREAM than in CON (Condition effect: p=0.0007). An OTC analgesic cream containing L-menthol and MS augmented cooling effects when cutaneously applied during TWI in exercise-induced hyperthermia. This was, at least in part, due to the counteractive vasodilatory effect of the analgesic cream. The cutaneous application of OTC analgesic cream may therefore provide a safe, accessible, and affordable means of enhancing the cooling effects of TWI.